Establishment of a highly specific detection system for GB virus C (GBV-C) minus-strand RNA - Seipp, Stefanie; Goeser, Tobias; Theilmann, Lorenz; Kallinowski, Birgit (Virus research, 1998)
Although the clinical relevance of GB virus C (GBV-C) is still elusive, this virus has been found with high prevalence in several groups of patients with liver disease. As was shown for hepatitis C virus (HCV), minus-strand RNA is supposed to function as a replicative intermediate. We have established a reliable and sensitive detection system for GBV-C minus-strand RNA based on nested RT-PCR (reverse transcription-polymerase chain reaction) with a tagged primer system. Sensitivity and specificity was extensively tested using in-vitro transcribed GBV-C sequences and genomic viral RNA. Specificity of the amplified fragments was proven by Southern blot hybridization. Using this detection system, we found the presence of GBV-C minus-strand RNA in 6/41 (14.6%) sera of GBV-C infected or GBV-C/HCV coinfected patients. No correlation with virological parameters such as amount of GBV-C plus-strand RNA, genotype or titer of HCV could be detected.